Application in Payment to Support Small, Micro, and Medium Enterprise - Sri Dewi Anggadini; Wulandari Dianti Putri (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
This study aims to determine whether e-Money boosts income in Small Micro Medium Enterprises. This study used descriptive quantitative method. Some people including SMEs entrepreneurs feel that making digital payments e-Money types are helpful in the transaction process because they are non-cash and can be keep in electronic devices minimizing risks of theft. E-Money or electronic money involved in the type of digital payment that involves the use of a computer network. The result of this paper is that E-money has many benefits for consumers, especially for MSMEs (Micro, Small, and Medium Enterprises) because its existence will shorten the time and cost of efforts to develop MSME businesses.